Comparison of thermal properties of Luffa-PCB and FR2 PCBs in power electronics circuit applications - Niyazi Gencer Gunduz; Ugur Kesen; Garip Genc (Ain Shams Engineering Journal)
Laminates of conventional printed circuit boards (PCBs) are created using epoxy resin and glass fiber. The most important recycling problems related to this card type can be briefly listed as the difficulties of e-waste collection, being very expensive and requires a very long time. Bio-PCBs seem to be offered as a solution to this problem. So, in this study, the thermal performances of Luffa and FR2 PCBs by a power electronic circuit were examined and compared. FTIR analysis was performed to characterize the chemical characterization of FR2 PCBs and Luffa-PCBs. In addition, the heat change of the circuit elements on the PCBs was able to compare clearly. According to the obtained results, it has been found that the produced Luffa-PCB circuit has adequate properties as an alternative to the traditional FR2 PCB circuit. Last of all, these results are very promising for solving the recycling problem of waste PCB boards.